A key role by polymers in microneedle technology: a new era. (2nd November 2021) - Rajput, Amarjitsing; Kulkarni, Madhur; Deshmukh, Prashant; Pingale, Prashant; Garkal, Atul; Gandhi, Sahil; Butani, Shital
Abstract: The skin serves as the major organ in the targeted transdermal drug delivery system for many compounds. The microneedle acts as a novel technique to deliver drugs across the different layers of the skin, including the major barrier stratum corneum, in an effective manner. A microneedle array patch comprises dozens to hundreds of micron-sized needles with numerous structures and advantages resulting from their special and smart designs. The microneedle approach is much more advanced than conventional transdermal delivery pathways due to several benefits like minimally invasive, painless, self-administrable, and enhanced patient compliance. The microneedles are classified into hollow, solid, coated, dissolving, and hydrogel. Several polymers are used to fabricate microneedle, such as natural, semi-synthetic, synthetic, biodegradable, and swellable polymers. Researchers in the preparation of microneedles also explored the combinations of polymers. The safety of the polymer used in microneedle is a crucial aspect to prevent toxicity in vivo . Thus, this review aims to provide a detailed review of microneedles and mainly focus on the various polymers used in the fabrication of microneedles.